Genome-wide analysis and expression profiling of the polyamine oxidase gene family in Solanum tuberosum L. - Xinyue Miao; Shenglan Wang; Yuqi Wang; Shengyang Cheng; Xiang Wang; Yue Chen (BMC Genomics)
Abstract Background Polyamine oxidase (PAO) is a crucial enzyme involved in the breakdown of polyamines (PAs) in plants. It not only regulates the levels of PAs, but also plays a role in the oxidative decomposition of PAs and the release of stress-related signals, contributing to the plant’s response and resistance to various adversities. While there have been numerous studies on the response of PAO to stress in other crops, there is a lack of research on this topic in potatoes, a major food crop. Results In this study, we aimed to explore the biological function of the StPAO gene in potato growth and development, as well as its expression patterns under stress. Using bioinformatics methods, we identified 14 StPAO genes in the potato genome. Protein sequence comparisons revealed a high similarity between the PAO proteins of potato and Arabidopsis. Chromosomal mapping and gene structure analysis showed that the StPAO genes were not evenly distributed on the chromosome and all contained an amino-oxidase domain. Furthermore, analysis of the promoters of these genes revealed the presence of abiotic and stress-related cis-acting elements, indicating their potential role in responding to different stresses. To investigate the expression patterns of these genes under stress, we used qRT-PCR to study their response to high temperature, drought, and ABA stress. Our results showed that StPAO6 and StPAO10 were significantly up-regulated under high temperature stress, indicating that they were involved in the process of potato resistance to high temperatures. Similarly, StPAO1, StPAO3, and StPAO4 were significantly up-regulated under drought stress, indicating their potential role in potatoes’ responses to drought. After ABA treatment, the expression levels of StPAO4, StPAO5, StPAO7, and StPAO14 were significantly up-regulated, suggesting their involvement in chemical defense mechanisms. Interestingly, the expression of StPAO11–13 was inhibited by all three stresses. Conclusions In conclusion, our study highlights the multifunctional nature of the StPAO gene family in potatoes, which plays a crucial role in coping with various stresses. This research deepens our understanding of the potato StPAO gene family and provides a reference for future studies on its function. It also serves as a theoretical basis for breeding stress-resistant potato varieties in the future.